2007
DOI: 10.1093/jn/137.7.1769
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavone-Rich Soy Protein Isolate Suppresses Androgen Receptor Expression without Altering Estrogen Receptor-β Expression or Serum Hormonal Profiles in Men at High Risk of Prostate Cancer

Abstract: The purpose of this study was to determine the effects of soy protein isolate consumption on circulating hormone profiles and hormone receptor expression patterns in men at high risk for developing advanced prostate cancer. Fifty-eight men were randomly assigned to consume 1 of 3 protein isolates containing 40 g/d protein: 1) soy protein isolate (SPI+) (107 mg/d isoflavones); 2) alcohol-washed soy protein isolate (SPI-) (<6 mg/d isoflavones); or 3) milk protein isolate (0 mg/d isoflavones). For 6 mo, the men c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 40 publications
3
65
0
Order By: Relevance
“…Anti-androgenic properties of genistein and equol were demonstrated both in vitro and in vivo. Both inhibit 5a-reductase enzyme (which converts testosterone to DHT) in human genital skin fibroblasts [7], and consumption of soy protein isolate by men at high risk of prostate cancer suppresses the expression of the AR [117]. In men, isoflavones concentrate in prostatic tissue and fluid [54,118].…”
Section: Prostate Cancermentioning
confidence: 99%
“…Anti-androgenic properties of genistein and equol were demonstrated both in vitro and in vivo. Both inhibit 5a-reductase enzyme (which converts testosterone to DHT) in human genital skin fibroblasts [7], and consumption of soy protein isolate by men at high risk of prostate cancer suppresses the expression of the AR [117]. In men, isoflavones concentrate in prostatic tissue and fluid [54,118].…”
Section: Prostate Cancermentioning
confidence: 99%
“…The 11 randomized diet-related clinical trials conducted to date are summarized in Table 1. The trials of single dietary constituents are featured fi rst [25], followed by those that tested multiple components [26][27][28][29][30], and fi nally trials involving functional foods [31][32][33][34] and multi-behavior interventions involving diet, exercise, and stress-management therapies [35•]. These 11 trials provide examples of the most rigorous dietary intervention trials conducted to date regarding prostate cancer, but there are still signifi cant limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is known that equol (particularly S-equol) has relatively high affinity for ER-β where it can act as a selective estrogen receptor modulator or SERM [19,25]. Previous laboratories, including ours, have shown that isoflavones binding to ER-β in the prostate can down regulate the AR and thus decrease negative androgen hormone actions [28]. Moreover, this may explain how isoflavonoid molecules accumulate in prostate tissue and prostatic fluid after oral supplementation [29,30].…”
Section: Discussionmentioning
confidence: 76%